ATLAS measurements of the properties of jets for boosted particle searches - Anduaga, Xabier Sebastián (2012)
Measurements are presented of the properties of high transverse momentum jets, produced in proton-proton collisions at a center-of-mass energy of √s=7TeV. The data correspond to an integrated luminosity of 35pb -1 and were collected with the ATLAS detector in 2010. Jet mass, width, eccentricity, planar flow and angularity are measured for jets reconstructed using the anti-kt algorithm with distance parameters R=0.6 and 1.0, with transverse momentum pT>300GeV and pseudorapidity |η|<2. The measurements are compared to the expectations of Monte Carlo generators that match leading-logarithmic parton showers to leading-order, or next-to-leading-order, matrix elements. The generators describe the general features of the jets, although discrepancies are observed in some distributions.